Determinan Pengungkapan Laporan Keuangan Pemerintah Provinsi di Indonesia - Evada Dewata; Muhammad Husni Mubarok; Lela Farantika Rahayu (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Regional government financial reports function as a form of public supervision and government accountability. The government must comply with disclosures in accordance with Government Accounting Standards (SAP) in its presentation. This research aims to analyze the influence of local revenue, the level of regional dependency, and audit findings on the level of disclosure of provincial government financial reports in Indonesia in 2018-2022. Samples were taken by purposive sampling of 155 local government financial reports, and data analysis was carried out using panel data regression with the Fixed Effect Model (FEM). The research results show that simultaneously, local original income, level of regional dependency, and audit findings have a positive effect on the level of financial report disclosure. However, partially, the level of regional dependence has a negative effect on the level of disclosure, while local revenue and audit findings have no effect on the level of disclosure.